Pengaruh Pembiayaan Perbankan Syariah Berdasarkan Sektor Ekonomi Terhadap Lingkungan Hidup di Indonesia dengan Inflasi Sebagai Moderasi - Dewi Rahmawati Maulidiyah; Vita Fatimatuzzahra; Sulistya Rusgianto (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to examine the effect of Islamic banking financing on the Environmental Quality Index with the inflation moderating variable. The Moderation Panel Data Regression Analysis was used in this study with samples from 33 provinces in Indonesia in 2010-2019 using non-probability sampling. The fixed effect model was chosen as the best model, using the inflation moderating variable shows that the mining and quarrying sector; the transportation, warehousing and communication sectors have a negative relationship, meaning that inflation can be a moderating variable. As for the manufacturing sector; electricity, gas, air sector; development sector; the trade, restaurant and hotel sectors have a negative and insignificant relationship and the agriculture, fishery and forestry sectors have a positive and insignificant relationship, inflation is also not moderate because high or low inflation doesn’t give effect on high financing that sectors, the focus of Islamic banking is on the real sector that drives energy consumption. Therefore, this research can serve as input for the Islamic Financial Institutions in prioritizing several environmentally friendly sectors to support Indonesia's green taxonomy, namely the service sector, the construction sector, the electricity, air and gas sector, the mining sector which have a positive but insignificant relationship because the market share of Islamic banking is still small compared to conventional banking.